2021
DOI: 10.1158/0008-5472.can-20-4243
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Therapies in Ovarian Cancer Alter Repetitive Element Expression in aTP53-Dependent Manner

Abstract: Epithelial ovarian carcinomas are particularly deadly due to intratumoral heterogeneity, resistance to standard-of-care therapies, and poor response to alternative treatments such as immunotherapy. Targeting the ovarian carcinoma epigenome with DNA methyltransferase inhibitors (DNMTi) or histone deacetylase inhibitors (HDACi) increases immune signaling and recruits CD8+ T cells and natural killer cells to fight ovarian carcinoma in murine models. This increased immune activity is caused by increased transcript… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 68 publications
3
22
0
Order By: Relevance
“…It has been reported that HMAs could cause the reexpression of endogenous retroviruses, which in turn trigger an IFN response ( 7 ). The transcriptomes of 9 paired specimens obtained before and after treatment were analyzed for differential expression of transposable elements (TEs) (see Supplemental Methods ) ( 21 , 22 ). We found that 21 TEs were differentially expressed between pre- and post-treatment specimens (FDR <0.05; Supplemental Table 8 ), supporting the idea that changes in the expression of retroviral elements are detectable in human tissue after HMA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that HMAs could cause the reexpression of endogenous retroviruses, which in turn trigger an IFN response ( 7 ). The transcriptomes of 9 paired specimens obtained before and after treatment were analyzed for differential expression of transposable elements (TEs) (see Supplemental Methods ) ( 21 , 22 ). We found that 21 TEs were differentially expressed between pre- and post-treatment specimens (FDR <0.05; Supplemental Table 8 ), supporting the idea that changes in the expression of retroviral elements are detectable in human tissue after HMA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Classon and colleagues implicated a specific H3K9 methylase, known to be critical for heterochromatin formation and maintenance (134). Chiappinelli et al reported increase in repeat element expression, another component in heterochromatic silenced regions (135). Finally, other studies implicate PRC2 and EZH2 in a similar mechanism (48, 136).…”
Section: Discussionmentioning
confidence: 99%
“…10 DNMTis remove the repressive methylation marks that silence DNA, allowing for transcription of transposable elements (TEs) that can form immunogenic double-stranded (ds)RNAs. [11][12][13][14][15] Interestingly, this DNMTi treatment of OC cells alters immunogenic dsRNA expression in a TP53-dependent manner. 13 We previously showed that cell lines with TP53 mutations have significantly higher baseline expression of immunogenic dsRNAs.…”
Section: Open Accessmentioning
confidence: 99%
“…[11][12][13][14][15] Interestingly, this DNMTi treatment of OC cells alters immunogenic dsRNA expression in a TP53-dependent manner. 13 We previously showed that cell lines with TP53 mutations have significantly higher baseline expression of immunogenic dsRNAs. Additionally, p53 activation increased expression of these immunogenic dsRNAs by binding directly to the TE loci.…”
Section: Open Accessmentioning
confidence: 99%